INTERPRETING THE CONDITIONS OF BULLYING IN PHOTOBOOK ENTITLED “BULLY” - Mulyono, Tanto Trisno; Astono, Rizky Andika Dwi (TOPLAMA, 2024)
This study aims to interpret the conditions of bullying as depicted in the photobook "Bully", exploring the symbolic and aesthetic elements used to represent the psychological and emotional dimensions of bullying. Utilizing a qualitative, interpretative approach, the research employs visual analysis and symbolic interpretation to uncover the deeper meanings conveyed through the photobook's imagery. The analysis focuses on how visual elements such as lighting, composition, and perspective reflect the dynamics of power, fear, isolation, and resilience within the context of bullying. The study is grounded in the Social-Ecological Model and Cognitive-Behavioral Theory, which provide frameworks for understanding the multifaceted nature of bullying and the cognitive distortions experienced by both victims and perpetrators. Results reveal that shadows in the images symbolize the psychological distress and cognitive distortions faced by victims and bullies, while light represents hope, resilience, and the potential for cognitive and emotional recovery. The photobook effectively captures the complex interplay between individual experiences and social influences, illustrating how both victims and bullies are affected by and respond to their environments. The findings underscore the importance of addressing both psychological and social factors in bullying interventions and highlight the photobook's role as a powerful medium for visualizing and understanding these dynamics.